2021
DOI: 10.33394/j-ps.v9i2.4374
|View full text |Cite
|
Sign up to set email alerts
|

Character education values: is learning process in elementary school implement it?

Abstract: This study aimed to determine the implementation of character education values at SDN 19 Rabangodu Utara, Bima City. The type of research used is mixed methods research with an exploratory design. This type of research combines qualitative and quantitative research. In this study, the researchers developed a questionnaire instrument and an observation sheet. Data collection techniques used in this study are observation, interviews (interviews), questionnaires (questionnaires), and documentation. The data analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In a similar vein, [17] reported the implementation of religious, honest, tolerance, discipline, self, love of country, respect for achievement, curiosity, communicative, caring environment, social care, and responsibility in State Elementary School Rampal Celaket 1 Malang. Also, [18] found that the students in Rabangodu Utara State Elementary School 19 showed the following character traits: religious, honest, diligent, disciplined, and caring/responsible.…”
Section: Type Of Characters Instilled At Schoolmentioning
confidence: 97%
“…In a similar vein, [17] reported the implementation of religious, honest, tolerance, discipline, self, love of country, respect for achievement, curiosity, communicative, caring environment, social care, and responsibility in State Elementary School Rampal Celaket 1 Malang. Also, [18] found that the students in Rabangodu Utara State Elementary School 19 showed the following character traits: religious, honest, diligent, disciplined, and caring/responsible.…”
Section: Type Of Characters Instilled At Schoolmentioning
confidence: 97%
“…The nature of an object that causes it to attract a person or group, what is meant by an object or object here is the value of character education. The character values that will be transformed in the learning process of Indonesian history, especially local history, include: Religious, Honesty, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, Spirit of Nationalism and Nationalism, Love for the Homeland, Respect achievement, communicative, love peace, love to read, care for the environment, care about social, responsibility (Pratiwi et al, 2021), (Hidayat et al, 2022).…”
Section: Character Education Valuesmentioning
confidence: 99%
“…sejalan dengan hasil temuan yang mengemukakan bahwa disiplin peserta didik pada masa pandemi mengalami penurunan karena beberapa faktor seperti menurunya motivasi belajar peserta didik, terbatasnya sarana dan prasarana, kurangnya waktu luang orang tua, serta penggunaan gawai yang berlebihan (Ni'mah & Setyawan, 2021). Menurut Pratiwi et al, (2021) kurangnya perhatian dari beberapa orang tua kepada siswa dan kebiasaan siswa online yang suka bermain menjadikan siswa memiliki kebiasaan tidak baik. Selain itu menurut Novianti & Garzia, (2020) memotivasi anak agar melakukan berbagai kegiatan baik merupakan tugas dari orang tua.…”
Section: Faktor Penyebab Terjadinya Tingkah Laku Indisiplinerunclassified